Pembuatan Plastik Biodegradable dari Pati biji Durian dan Pati Biji Nangka - Rozikhin; Farida Hanum Hamzah; yelmira zalfiatri (CHEMPUBLISH JOURNAL, 2020)
Durian seeds and jackfruit seeds are agricultural waste containing high starch, which can be used as raw material for biodegradable plastic. The purpose of this research was to get the best formulation on the making of biodegradable plastic based on starch of durian seed and starch of jackfruit seed with addition of beeswax. This research was conducted experimentaly by using complete randomized design (CRD) which consists of five treatments and three replications, thus analysis of variance (ANOVA) and followed by Duncan’s New Multiple Range Test (DNMRT) at level 5%. The treatments in this research were P1 (starch of jackfruit seed 5%), P2 (starch of durian seed 1,25% : starch of jackfruit seed 3,75%), P3 (starch of durian seed 2,5% : starch of jackfruit seed 2,5%), P4 (starch of durian seed 3,75% : starch of jackfruit seed 1,25%), and P5 (starch of durian seed 5%) in formulation of biodegradable plastic. The best treatment was P2 which has a thickness of 0,76 mm, water resistance of 59,19%, water vapor transmission rate of 4,53 g/cm2/h, tensile strength of 21,57 MPa, and elongation of 6,58%.